1993
DOI: 10.1037/0278-7393.19.2.295
|View full text |Cite
|
Sign up to set email alerts
|

Effects of familiarity and aptness on metaphor processing.

Abstract: A cross-modal priming paradigm was used to examine the comprehension of metaphors varying in familiarity and aptness. In Experiments 1 and 2 high-familiar metaphors showed availability of the figurative meaning, but low-familiar (LF) metaphors did not. In Experiment 3, only LF metaphors that had been rated highly apt showed evidence of figurative activation. Experiment 4 showed evidence of figurative activation for most LF and moderate-apt metaphors. The locus of activation was investigated in Experiment 5 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
182
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(204 citation statements)
references
References 30 publications
20
182
1
1
Order By: Relevance
“…Compared with the average lexical decision time and accuracy rate reported in the literature (e.g., Blasko & Connine, 1993;Swinney, Love, Walenski, & Smith, 2007), the participants' performances on the lexical decision task, including speed (M = 609, SD = 124) and accuracy (M = 97%, SD = 3%), were comparable to reports by studies using the priming approach, which indicates their attentiveness to the task. Participants' responses to the recognition task were categorized as hits or false alarms.…”
Section: Resultssupporting
confidence: 68%
“…Compared with the average lexical decision time and accuracy rate reported in the literature (e.g., Blasko & Connine, 1993;Swinney, Love, Walenski, & Smith, 2007), the participants' performances on the lexical decision task, including speed (M = 609, SD = 124) and accuracy (M = 97%, SD = 3%), were comparable to reports by studies using the priming approach, which indicates their attentiveness to the task. Participants' responses to the recognition task were categorized as hits or false alarms.…”
Section: Resultssupporting
confidence: 68%
“…For example, using a word fragment completion task, Giora and Fein (1999) found that both literal and metaphoric meanings were activated in the comprehension of familiar metaphors. Similarly, using the cross-modal priming technique, Blasko and Connine (1993) found priming for the literal as well as the metaphoric meanings in familiar metaphors. For unfamiliar metaphors, they found priming only for the literal meanings of their stimuli.…”
Section: Experimental Evidencementioning
confidence: 99%
“…For instance, familiarity, one such variable, is a determinant of processing difficulty for literal and nonliteral language alike (Gernsbacher, 1984). In a cross-modal priming study, Blasko and Connine (1993) showed that the familiarity of a metaphor affected reaction times for words related to its metaphorical meaning. In an eye-tracking study, Blasko and Briihl (1997) found that gaze durations for metaphorical expressions decreased as both a function of familiarity and a function of contextual support.…”
Section: Processing Metaphoric Languagementioning
confidence: 99%
“…This means that the process of metaphor understanding makes use of the basic-level meaning of shark, and, therefore, that concept should be activated in memory. Indeed, Blasko and Connine (1993) provided evidence for the activation of the literal meaning of metaphor vehicles as people hear metaphorical sentences. Using a cross-modal priming paradigm, they demonstrated that immediately following the vehicle of the metaphor, hard work is a ladder, the concept rungs was activated.…”
Section: Comprehension Mechanisms and Metaphor Understandingmentioning
confidence: 99%